MEMBANGUN REMAJA SEHAT UNTUK MEWUJUDKAN PRIBADI YANG BERAKHLAK MULIA - Heri Saptadi Ismanto; Joko Sulianto; Mudzanatun IKIP PGRI Semarang; Ryky Mandar Sari (Universitas PGRI Semarang, 2012)
AbstractParents have a vital role for growth and development of a teenager. Parents as the first actor to be an example for a teenager, so it must equip children with knowledge of the personality and the science of religion that later children can socialize in the community. Juvenile delinquency is happening is not the fault of the parents themselves, but also lies in the surrounding environment that can affect the behavior of adolescent youth. The role of parents and the environment is important for teens to form personal the better. In dealing with teenagers there are some things you should always keep in mind, namely that the soul is a soul-filled adolescent turmoil. Internal and external conditions are equally turbulent adolescence that causes more prone than other stages of mental development of adolescents. To reduce collisions between turbulence and to provide opportunities for youth to develop themselves in a more optimal, need to be created nearby environmental conditions as stable as possible, especially the family environment.Key Words: Adolescents, Personal, Moral HonorAbstrakOrang tua memiliki peran yang sangat penting terhadap tumbuh kembang seorang remaja. Orang tua sebagai aktor pertama yang menjadi contoh bagi seorang remaja, sehingga harus membekali anak dengan ilmu kepribadian dan ilmu agama supaya kelak anak dapat bersosialisasi dimasyarakat. Kenakalan remaja yang terjadi bukanlah kesalahan dari orang tua sendiri, melainkan juga terletak pada lingkungan disekitar remaja yang dapat mempengaruhi perilaku remaja. Peran orang tua dan lingkungan sekitar sangatlah penting untuk membentuk pribadi remaja agar menjadi lebih baik. Dalam menghadapi remaja ada beberapa hal yang harus selalu diingat, yaitu bahwa jiwa remaja adalah jiwa yang penuh gejolak. Kondisi intern dan ekstern yang sama-sama bergejolak inilah yang menyebabkan masa remaja lebih rawan daripada tahap-tahap lain perkembangan jiwa remaja. Untuk mengurangi benturan antargejolak itu dan untuk memberi kesempatan agar remaja dapat mengembangkan dirinya secara lebih optimal, perlu diciptakan kondisi lingkungan terdekat yang sestabil mungkin, khususnya lingkungan keluarga.Kata Kunci: Remaja, Pribadi, Akhlak Mulia